2007
DOI: 10.1111/j.1365-2109.2007.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary leucine requirement of fingerling Indian major carp, Labeo rohita (Hamilton)

Abstract: An 8-week feeding experiment was conducted to evaluate the dietary leucine requirement of ¢ngerling Indian major carp, Labeo rohita (3.50 AE 0.04 cm; 0.40 AE 0.02 g) using amino acid test diets (40% crude protein; 17.90 kJ g À1 gross energy) containing casein and gelatin as intact protein sources and L-crystalline amino acids. Growth performance and biochemical parameters were assessed by feeding six amino acid test diets supplemented with graded concentrations of leucine (0.75, 1.0, 1.25, 1.50, 1.75 and 2.0 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 46 publications
9
67
1
Order By: Relevance
“…The result is close to that of 6.98% of dietary protein for bluntnose black bream (Megalobrama amblycephala) (Li, 1996), but higher than those reported for many other fish, e.g. 3.75%−3.92% of dietary protein for Indian major carp (Hamilton) (Abidi and Khan, 2007), 5.2% of dietary protein for Atlantic salmon (Salmon salar L.) (Rollin, 1999), 3.7% of dietary protein for catla (Catla cacia) (Ravi and Devaraj, 1991), 3.5% of dietary protein for channal catfish (Ictalurus punctatus) (Wilson et al, 1980), 3.9% of dietary protein for chinook salmon (Oncorhynchus keta) (Chance et al, 1964) and 4.3% of dietary protein for both European seabass (Morone labrax) (Kaushik, 1998) and white sturgeon (Acipenser transmontanus) (Ng and Hung, 1995).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The result is close to that of 6.98% of dietary protein for bluntnose black bream (Megalobrama amblycephala) (Li, 1996), but higher than those reported for many other fish, e.g. 3.75%−3.92% of dietary protein for Indian major carp (Hamilton) (Abidi and Khan, 2007), 5.2% of dietary protein for Atlantic salmon (Salmon salar L.) (Rollin, 1999), 3.7% of dietary protein for catla (Catla cacia) (Ravi and Devaraj, 1991), 3.5% of dietary protein for channal catfish (Ictalurus punctatus) (Wilson et al, 1980), 3.9% of dietary protein for chinook salmon (Oncorhynchus keta) (Chance et al, 1964) and 4.3% of dietary protein for both European seabass (Morone labrax) (Kaushik, 1998) and white sturgeon (Acipenser transmontanus) (Ng and Hung, 1995).…”
Section: Discussionsupporting
confidence: 78%
“…Although leucine is considered to be essential for normal growth and reproductive potential of fish, imbalance of dietary leucine could lead to a reduction in growth rate (Abidi and Khan, 2007). In the present study, higher amount of leucine was found to depress the growth of large yellow croaker.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These negative effects of leucine at high level may be related to accumulation of leucine itself or its metabolites. Abidi and Khan (2007) indicated that excessive leucine leads to the high oxidation to ketones and accumulation of other toxic metabolite. In cerebral cortex of rats, the accumulation of leucine and its metabolite inhibited activities of antioxidant enzymes CAT and GPx, thus leading to oxidative damage (Bridi et al, 2005).…”
Section: −1mentioning
confidence: 99%
“…The dietary protein level was fixed at 300 g kg − 1 , reported optimum for the growth of grass carp (Khan et al, 2004). The mixture of crystalline amino acids without leucine was prepared according to the method described by Abidi and Khan (2007). Our previous study observed that the optimal leucine requirement for growth is 13.0 g kg −1 diet (Deng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%